Hematological Profiles in European Seabass (Dicentrarchus labrax): Methodological Variability, Analytical Constraints and Implications for Reference Value Interpretation - Sevasti-Aliki Kounida; Michail-Aggelos Valsamidis; Sofia Pappou; Vasileios Bakopoulos (Fishes, 2026)
European seabass (Dicentrarchus labrax) hematology is widely used in nutrition, welfare, stress and health studies, yet results from different laboratories are often difficult to compare. This critical narrative review examines how preanalytical handling, analytical procedure and biological context affect that comparability. It is written for researchers, diagnostic laboratories and aquaculture health teams that collect or use D. labrax blood data. Primary European seabass studies are discussed directly where they provide quantitative operating conditions, method comparisons or measurable biological changes. Manual microscopy, automated analyzers and flow cytometry are considered separately because nucleated erythrocytes and thrombocytes create different sources of error in each approach. The review distinguishes practical quality-control checks from the fuller reporting required for reproducibility and separates published operating conditions from numerical limits that have not been validated for the species. Seasonal studies show large coordinated shifts in red blood cell count (RBC), hemoglobin concentration (Hb) and hematocrit (Hct), whereas white blood cell count (WBC) and thrombocyte results remain particularly dependent on cell definition and analytical method. Published pooled estimates are useful for broad comparison but not as universal diagnostic limits. The most defensible use of European seabass hematology is therefore within a defined population, a stated sampling protocol and a method whose performance is known for the intended measurement.

Assessing the impact of gram-negative bacteria on the common octopus, in relation to rising sea temperature: a study of total protein concentration and hemolysis activity in hemolymph - Daniella-Mari White; Emmanouela Karaveti; Vasileios Bakopoulos (Journal of Invertebrate Pathology, 2026)

Lysozyme Activity in the Hemolymph of Octopus vulgaris (Cuvier, 1797) Following Challenge with Gram-Negative Bacteria: Insights into Temperature-Driven Innate Immune Response - Daniella-Mari White; Eleni Anastasiadou; Michail-Aggelos Valsamidis; Vasileios Bakopoulos (Fishes, 2025)
As aquaculture expands globally, understanding immune responses in non-traditional farmed species like Octopus vulgaris under varying environmental conditions is increasingly important. This study investigated lysozyme activity, a key innate immune marker, in cell-free hemolymph of O. vulgaris following experimental challenge with four Gram-negative fish pathogens (Photobacterium damselae subsp. piscicida, P. damselae subsp. damselae, Vibrio alginolyticus, and V. anguillarum O1) at two temperatures (21 ± 0.5 °C and 24 ± 0.5 °C). These pathogens were selected because octopus farming frequently occurs near fish aquaculture facilities, raising the potential for pathogen crossover. A total of 216 wild octopuses were injected intramuscularly or intravenously and sampled on days 0, 3, and 7 post-challenge. Lysozyme activity varied by pathogen, injection route, sampling time, and temperature. A significant time- and temperature-dependent increase was observed, especially in IM-challenged groups exposed to Photobacterium species. Elevated temperatures supported a more prolonged immune response. These results highlight lysozyme as a responsive biomarker of innate immunity in O. vulgaris and emphasize the role of environmental factors in immune modulation. This work provides a foundation for disease monitoring and health management in cephalopod aquaculture. Future research should examine long-term lysozyme dynamics, broader pathogen exposure, molecular mechanisms, and additional environmental stressors such as salinity and pollution.

Refining the Occurrence of Viral Encephalopathy and Retinopathy, Photobacteriosis, and Vibriosis in Connection with Seawater Physicochemical Parameters: A Five-Year Case Study - EFTHIMIOS SPINOS; GEORGE KATSELIS; MICHAIL AGGELOS VALSAMIDIS; MARI DANIELLA WHITE; VASILEIOS BAKOPOULOS (Mediterranean Marine Science, 2024)
The marine environment and its physicochemical parameters play a pivotal role in the context of fish farming. Fundamental physicochemical factors of water, including temperature (T°C), salinity (S psu), dissolved oxygen (D.O. mg/l), and pH, exert a profound influence on the physiology of farmed aquatic animals and the composition of microbial communities. This study aimed to establish correlations between documented disease occurrences in sea bass intensive rearing and the prevailing physicochemical parameters of water. The objective was to analyse the significance of these parameters in disease outbreaks and develop a predictive model for the outbreak risk of key diseases. To this end, real-time physicochemical data were collected daily over five years (2011-2015) from two fish farms (A and B) located in the Gulf of Argostoli, island of Cephalonia, Western Greece. The focus was on incidences of Viral Encephalopathy and Retinopathy (VER), Photobacteriosis caused by Photobacterium damselae subsp. piscicida (PHDP) and Vibriosis caused by Vibrio anguillarum serotype O1 (VAO1). Statistically significant correlations were found between increasing water temperature and salinity and the occurrence of VER, PHDP, and VAO1 diseases. The reduction of dissolved oxygen, when combined with other parameters, synergistically triggered the manifestation of these three diseases. The study’s findings were discussed within the context of their potential to predict disease outbreaks based on fluctuations in the physicochemical parameters of water and anticipated climate change scenarios.

Correlations of betanodavirus load in the brain of experimentally infected sea bass (Dicentrarchus labrax, L.) with varying levels of resistance to viral nervous necrosis - VASILEIOS BAKOPOULOS; ANASTASIA PANAGIOTAKI; MICHAIL-AGGELOS VALSAMIDIS; DANIELLA-MARI WHITE; LEONIDAS PAPAHARISIS; ARKADIOS DIMITROGLOU; ELLI KAKAVA (Mediterranean Marine Science, 2023)
The red-spotted grouper nervous necrosis virus (RGNNV) genotype of Betanodavirus causes significant losses to the European sea bass aquaculture industry. The lack of widely available vaccines against this genotype has led researchers and the industry to investigate other avenues for reducing mortality caused by the disease, such as the selection of resistant stocks. The objectives of this study were: a) to assess the presence of natural resistance in sea bass families propagated in the genetic improvement program of Nireus S.A., Greece and, b) to test an ELISA method able to detect viral coat antigen and measure viral load in the brain of tested fish. The second objective was to investigate virus antigen fluctuations during the course of the infection and its correlation with disease development, mortality and resistance. Further aspects of disease pathogenesis were investigated. A population of sea bass consisting of 89 families was experimentally infected with an RGNNV genotype of Betanodavirus; mortalities were recorded and brain samples from dead and survived fish were collected. Experimental infection of fish resulted in a typical pattern of mortality development that reached 56%. Different levels of natural resistance between families were found with cumulative mortality ranging from 20% to 86.2%. There was no statistical difference between the weight of dead fish and the resistant and susceptible families, except when extreme phenotypes were tested, indicating that the weight of fish that died was not a significant factor of final mortality. Brain virus load in the population as a whole increased sharply until D6 post-infection and then gradually dropped until the end of the experiment. When the viral load in the population (dead and survived fish) was tested against time of death, no correlation was found. In fish that survived the infection, the virus load remained high. The viral load per mg of brain tissue in samples taken from dead fish was not a factor that influenced family cumulative % mortality. Brain samples from survived fish reproduced the disease after infection of healthy fish. This study revealed a natural resistance of sea bass to Betanodavirus infection. This important finding can be used as an additional tool in reducing the mortality of cultured stocks. Additionally, there was clear evidence that fish surviving infection become subclinical carriers of the pathogen. Apparently, survival may not be associated with mechanisms of viral clearance but to other mechanisms that may suspend viral replication or aid infected cell endurance. These findings may assist in developing future vaccines and stock selection. A combination of effective vaccination and resistant stocks could be the way ahead.

Immune response of European sea bass (Dicentrarchus labrax L.) against combination of antigens from three different pathogens - Michail-Aggelos Valsamidis; Daniella-Mari White; Giorgos D. Kokkoris; Vasileios Bakopoulos (Veterinary Immunology and Immunopathology, 2023)

Length – Weight Relationships of 12 Commercial Fish Species Caught with Static Fishing Gear in the N. Ionian Sea (Greece) - Athanasios Evagelopoulos; Ioannis E. Batjakas; Efthimios Spinos; Vasileios Bakopoulos (Thalassas: An International Journal of Marine Sciences, 2020)